2017
DOI: 10.1002/2211-5463.12310
|View full text |Cite
|
Sign up to set email alerts
|

Deep sequencing and comprehensive expression analysis identifies several molecules potentially related to human poorly differentiated hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) that is graded histologically as poorly differentiated has a high recurrence, metastasis and poor prognosis. We sought to determine the regulatory mechanisms of HCC tumorigenesis and to identify molecules closely related to poorly differentiated HCC. High‐throughput sequencing was used to construct microRNA (miRNA) and mRNA expression profiles for poorly differentiated HCC tissues and adjacent tissues. Network analysis was carried out to study miRNA–target interactions. Integrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…IGF2BP3, a RNA‐binding protein, has been reported to be associated with HCC progression . Thus, we aimed to determine whether IGF2BP3 interacted with LINC00467 (or TRAF5) in HCC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…IGF2BP3, a RNA‐binding protein, has been reported to be associated with HCC progression . Thus, we aimed to determine whether IGF2BP3 interacted with LINC00467 (or TRAF5) in HCC.…”
Section: Resultsmentioning
confidence: 99%
“…IGF2BP3, a RNA-binding protein, has been reported to be associated with HCC progression. 18,19 Thus, we aimed to determine whether IGF2BP3 interacted with LINC00467 (or TRAF5) in HCC. To verify the speculation, starBase (http://starbase.sysu.edu.cn) was utilized, which indicated that LINC00467 could possibly bind with IGF2BP3 ( Figure 3A).…”
Section: Linc00467 Promotes the Mrna Stability Of Traf5 By Binding mentioning
confidence: 99%
“…Among these 13 hub genes, 4 ( C8ORF33 , STIP1 , Hsp90AB1 and PRKDC ) have been implicated in HCC behaviour by previous studies [ 28 – 31 ]. C8ORF33 has been associated with OS in HCC patients and could be used to distinguish poorly differentiated from well differentiated HCCs [ 28 ]. STIP1 acts as an adaptor protein that coordinates functions of HSP70 and HSP90 in protein folding, and as a secretory protein that regulates malignant cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is one of the most common malignancies, with high incidence and mortality, especially among East Asian and sub‐Saharan African populations . Unfortunately, the efficacy of current therapeutic strategies for HCC is unsatisfactory , leading to poor prognosis and high recurrence rate after surgical resection of primary tumors .…”
Section: Introductionmentioning
confidence: 99%